2018
DOI: 10.1017/s0007114518000181
|View full text |Cite
|
Sign up to set email alerts
|

Leucine promotes differentiation of porcine myoblasts through the protein kinase B (Akt)/Forkhead box O1 signalling pathway

Abstract: Leucine, one of the branched-chain amino acids, is the only amino acid to regulate protein turnover in skeletal muscle. Leucine not only increases muscle protein synthesis, but also decreases muscle protein degradation. It is well documented that leucine plays a positive role in differentiation of murine muscle cells. However, the role of leucine on porcine myoblast differentiation and its mechanism remains unclear. In this study, porcine myoblasts were induced to differentiate with differentiation medium cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 35 publications
2
17
0
Order By: Relevance
“…The modulation of skeletal muscle mass depends on the balance between protein synthesis and degradation. Previous studies have shown a reduction in protein degradation after branched-chain amino acids or leucine administration through changing the expression of Foxo1, MAFbx and MuRF-1 [42][43][44][45], which play an essential role in promoting muscle proteolysis [46]. Consistent with these studies, our result showed that increased amino acid profile after fermentation decreased the abundance of Foxo1 and MAFbx.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The modulation of skeletal muscle mass depends on the balance between protein synthesis and degradation. Previous studies have shown a reduction in protein degradation after branched-chain amino acids or leucine administration through changing the expression of Foxo1, MAFbx and MuRF-1 [42][43][44][45], which play an essential role in promoting muscle proteolysis [46]. Consistent with these studies, our result showed that increased amino acid profile after fermentation decreased the abundance of Foxo1 and MAFbx.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with these studies, our result showed that increased amino acid profile after fermentation decreased the abundance of Foxo1 and MAFbx. Additionally, a previous study reported that leucine also increased the mRNA and protein levels of MyoG and MyoD [42], which was an important regulator of myogenesis [47]. Similarly, we also observed an increased expression of MyoD by the fermented feed that was rich in amino acid profile.…”
Section: Discussionsupporting
confidence: 85%
“…This result was in good agreement with reports on C2C12 myoblasts, preterm rat satellite cells, and porcine myoblasts. These studies reported that Leu limitation prevents the differentiation of myoblasts and primary satellite cells [24][25][26]. Chen et al also demonstrated that Leu could promote proliferation of C2C12 myoblasts [76].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, these studies mainly focused on the effects of Leu on growth, protein retention, and immunity. Recently, studies in primary preterm rat satellite cells and porcine myoblasts showed Leu promoted proliferation and differentiation [24,25]. Averous et al (2012) also reported Leu deficiency inhibited the differentiation of both C2C12 myoblasts and primary mice satellite cells through regulating Myf5 and MyoD expression [26].…”
Section: Introductionmentioning
confidence: 99%
“…Porcine myoblasts were isolated form 3-d-old male Duroc Ɨ Landrace Ɨ Yorkshire pigs. The cells were isolated as described previously (25) . When the density reached about 80 % confluence, the cells were shifted to differentiation medium containing Dulbecco's modified Eagle's medium (DMEM)/F12 with 2 % horse serum (Invitrogen).…”
Section: Culture and Treatment Of Porcine Myoblastsmentioning
confidence: 99%